Examining the nuance in adolescents' police encounters: Positive, negative, or both?. Issue 1 (6th July 2022) - Fix, Rebecca L.; Jackson, Dylan B.; Jindal, Monique
Abstract: Youth−police encounters reflect a pivotal point for intervention to improve police−community relations. Data from 454 youths ( M  = 15.1 years) included brief written descriptions of positive and negative experiences with a police officer and perceptions of police using Likert‐scale items. Participating youths described both positive (46%) and negative (60%) experiences with police. Besides decidedly positive experiences, youths also responded to the positive experiences prompt with ambiguous situations (46%) that involved the arrest of the youth or their family (procedural or distributive justice). Examples of ambiguous self‐described positive experiences included, "Restraining order, " "My dad went to prison, " and "When I was arrested in location redacted, the officer was kind and didn't put me in cuffs." Results from regressions indicated youths' perceptions of police were more often associated with the absence of positive experiences than specific positive or negative experiences. Study findings have implications for police trainings and future research on youth−police encounters.